(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
The priority areas of the state policy for the development of health care are the protection of children’s and adolescents’ health, timely provision of their high-quality and effective medical care and the organization of an active fight against non-communicable diseases. As part of the health care reform, government decrees have changed the principles of providing specialized allergological care to patients - its structure, management, which has led to the need to improve the system of providing medical care and prevention to children with allergic diseases in the Republic of Uzbekistan. The health of children is often considered one of the most reliable indicators of the degree of environmental pollution. The literature has accumulated a fairly large number of facts indicating a direct relationship between the health of the child population and the levels of air pollution. It has been established that harmful environmental factors can cause the development of chronic pathology of all organs and systems, in particular: the immune system, respiratory organs, gastrointestinal tract, liver, endocrine and a number of other systems. Large industrial cities are turning into centers of acute environmental problems. According to epidemiological studies, 25-30% of the population of developed industrial countries have various allergic manifestations [1,3]. One of the reasons for the development of allergic diseases in children is environmental pollution factors, living in an ecologically unfavorable area. Unfavorable environmental factors can act directly as allergens [2]. The problem of the relationship between the state of the environment and human health in the Republic of Uzbekistan is becoming increasingly relevant every year. Taking this fact into account, the Government of the country and the Ministry of Health pay great attention to the problems of early diagnosis of diseases and rehabilitation of frequently ill children. The President of the country I. Karimov declared 2016 the year of "Healthy Mother and Child". Pollution of the natural environment and its impact on human health are closely correlated with each other, which can be seen when analyzing data on the incidence rate, emissions of pollutants into the atmosphere from stationary sources, discharge of contaminated wastewater into water bodies, formation of toxic waste, accessibility of the population to drinking water and water quality, etc.